2007
DOI: 10.1002/elps.200700314
|View full text |Cite
|
Sign up to set email alerts
|

CE: A useful analytical tool for the characterization of Maillard reaction products in foods

Abstract: The Maillard reaction (MR) is a complex series of nonenzymatic reactions between reducing compounds and amines, amino acids, peptides, or proteins that play an important role in the formation of flavors and colors in foods during processing and storage. Also, the antioxidant properties of some Maillard reaction products (MRP) was an additional benefit reported. On the other hand, these reactions decrease the nutritional quality of foods and may result in the formation of toxic MRP. Although, research to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…This intensity range, covered by the ICR mass analyser, can also be interpreted as an approximation for the relative concentration range in which compounds occur in the MR. The similarity in chemical properties together with the complexity and high dynamic range in concentrations makes a simultaneous or comprehensive analysis with conventional analytical approaches, such as LC-MS, very challenging 7 , 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This intensity range, covered by the ICR mass analyser, can also be interpreted as an approximation for the relative concentration range in which compounds occur in the MR. The similarity in chemical properties together with the complexity and high dynamic range in concentrations makes a simultaneous or comprehensive analysis with conventional analytical approaches, such as LC-MS, very challenging 7 , 8 .…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, non-volatiles of the intermediate phase are still unknown to a large extent. The high diversity in chemical properties makes a simultaneous analysis especially challenging 7 , 8 . Although several reported methods have successfully separated and detected multiple reaction products, non-targeted analysis exploring the non-volatiles, produced throughout the course of the MR, are rare 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Preliminarly we have observed that consumption of powdered milk explains up to 20% of CML serum concentration in type 2 diabetics (unpublished data). Our group continues to investigate on this area, because numerous studies also confirm that "westernized" dietary patterns, with high intakes of processed foods, increase circulating, urinary and tissue AGEs [16][17][18], and adversely affect the expression of receptors, activating de inflammatory cascade [19]. This is extremely relevant for the growing diabetic population, rapidly increasing among Latin Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the mentioned period, several reviews have been published focusing in applications of CE to analyze specific group of compounds with potential interest in food analysis, including polyphenols 2, proteins and peptides 3–6, non‐protein amino acids (AA) 7, Maillard reaction products 8, metabolites 9, organic acids 10, micronutrients 11, food contaminants and residues 12, antibiotics 13, microbial contaminants and toxins 14–17, additives and organic contaminants 18, 19 and inorganic ions 20. A comprehensive review based on the use of LC and CE for the analysis of soybean proteins and their hydrolyzates to study the nutritional, functional and biomedical properties of different soybean cultivars has also been published 21.…”
Section: Introductionmentioning
confidence: 99%